Implementasi Kepemilikan Emas dengan Akad Murabahah pada Produk Solusi Emas Hijrah di Bank Muamalat KCP Parepare - Nurfitria Hidayatillah; Mutiara Nasir; Khumaerah, Kamila; Natsir, Ahmad Nizar (Yayasan Literasi Sains Indonesia, 2025)
This research aims to analyze the implementation of Gold Ownership Financing (PKE), specifically the 'Solusi Emas Hijrah' product by Bank Muamalat KCP Parepare. It focuses on the dual akad (contract) structure of Murabahah Tanpa Wakalah (cost-plus sale without agency) and Rahn (pawn/collateral), as well as Sharia compliance and regional operational risk mitigation. The background problem arises from the tension between the demand for installment-based gold investment and the classic Fiqh Muamalah principle requiring spot (cash) transactions for gold sales (yadan bi yadin). The main findings indicate that the Solusi Emas Hijrah product is normatively compliant, achieved through fixing the total sale price over the financing tenor of up to 120 months (ensuring there is no riba al-nasi’ah or deferred interest), and the mandatory pledging of the 24-karat gold through the Rahn contract, where itis stored by the bank until the financing is settled. The pledged gold must be stored centrally in the Head Office/Main Branch Treasury (Khasanah Kantor Pusat/KCU), not at KCP Parepare, due to the Sub-Branch Office's (KCP) infrastructure limitations. This centralization is effective in mitigating physical security and credit risk, where late payment fines are allocated to the Charity Fund (Dana Kebajikan), but simultaneously increases operational risk related to the logistics and chain of custody of assets at KCP Parepare.